PENILAIAN KINERJA UPK PUTI BUNGSU KECAMATAN TANJUNG EMAS DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD - Sri Madona Saleh; Desy Farina; Rafida Sofiana (Jurnal Manajemen Bisnis Syariah, 2021)
This study aims to assess the performance of UPK Puti Bungsu, Tanjung Emas District using the Balanced Scorecard approach. The assessment technique used in this study is an assessment of the four Balanced Scorecard perspectives, namely: financial perspective, customer perspective, internal business process perspective and learning and growth perspective. This type of research is field research using quantitative descriptive methods. The data used in this study are primary data in the form of interviews and questionnaires, secondary data. The results of this study indicate that, based on a financial perspective, seen from the Net Perform Loan ratio in 2015 1%, 2016 1% and 2017 1.50%, seen from Idle Cash in 2015 amounted to 0.47%, 2016 1.19% and 2017 amounted to 2.53% and seen from the Capital Growth in 2015 34.76%, 2016 amounted to 9.86% and in 2017 amounted to 50.76 %, seen from the customer perspective, UPK Puti Bungsu, Tanjung Emas District has a good performance. This is indicated by the large number of members who expressed satisfaction by the SPP group members of the UPK Puti Bungsu service. Viewed from the perspective of the internal business process, the performance of UPK Puti Bungsu, Tanjung Emas District for the innovation process is good, seen from the perspective of growth and learning the performance of UPK Puti Bungsu can be seen from the large number of satisfied employees of UPK Puti Bungsu with management and training at UPK Puti Bungsu. Tanjung Emas District and increasing worker productivity.